Coating composition, coating, and preparation method and application of coating
By using the high lubricity coating formed by the coating composition in the LPCVD process, the corrosion problem caused by the direct contact between the metal matrix and the polysilicon layer is solved, the corrosion resistance and service life of the metal matrix are improved, and process pollution is reduced.
Patent Information
- Application Number
- CN202411295364.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the low pressure chemical vapor deposition (LPCVD) process, contact between the metal matrix and the polysilicon layer causes erosion of metal parts, thereby reducing service life and increasing costs.
A coating composition is adopted, including 30% to 70% by weight of film forming material and 30% to 70% by weight of composite filler, which consists of boron nitride, graphite, alumina, etc., to form a coating with high lubricity. Used for the surface of the metal matrix to block the polysilicon layer and prevent it from erosion.
Improve the lubricity, high temperature resistance, oxidation resistance and corrosion resistance of the metal matrix surface, effectively block the direct contact between polycrystalline silicon and metal matrix, slow down the erosion of polycrystalline silicon on the metal matrix, and prevent it from being high lubricity and good binding force. Polysilicon aggregation and shedding to reduce process pollution.
Smart Images

Figure CN119192885A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and in particular to a coating composition, a coating, a preparation method of the coating, and an application thereof. Background Art
[0002] The core process of TOPCon solar cell processing is the process of making tunnel oxide layer and polysilicon layer. The preparation methods of the above two film layers can be divided into low pressure chemical vapor deposition (LPCVD), plasma enhanced chemical vapor deposition (PECVD) and physical vapor deposition (PVD). The LPCVD process uses LPCVD equipment to grow silicon oxide layer and deposit polysilicon by thermal oxidation.
[0003] LPCVD is one of the important processes for depositing α-Si / polysilicon layers under low pressure conditions. In this process, since the process gas required for the reaction needs to be introduced into the furnace tube during the deposition process, the gas needs to be transported to the corresponding position of the furnace tube through the air inlet pipe, which is usually made of metal; in addition, since the gas reaction requires a high temperature environment, the furnace door needs to be sealed, and there will be a large temperature difference when entering and leaving the boat, so a certain number of metal insulation sheets or insulation boards are usually placed near the furnace tube mouth to prevent the heat in the furnace from directly impacting the outside and blocking a certain amount of heat. However, since the process gas will react to deposit polysilicon in the furnace tube, a large amount of polysilicon layer will be deposited on the surface of the air inlet pipe and the metal insulation board. The polysilicon layer will cause serious erosion to metal materials such as the air inlet pipe and the metal insulation board, which will cause the failure of parts, reduce the service life of parts, and increase costs. In addition to the air inlet pipe and the metal insulation board, the above problems will also exist in parts such as metal furnace tubes, flow barrels, and flow plates. Summary of the invention
[0004] In view of this, in order to solve at least one of the above defects, it is necessary to provide a coating composition for metal surface with high lubricity, which can improve the corrosion resistance of metal and prevent polysilicon erosion.
[0005] In addition, the present application also provides a coating formed using the aforementioned coating composition, a method for preparing the coating, and a coating device for applying the coating.
[0006] An embodiment of the present application provides a coating composition, the raw materials of which include: 30wt% to 70wt% of a film-forming substance and 30wt% to 70wt% of a composite filler, wherein the composite filler includes: a first component, a second component and a third component, the first component includes: at least one of boron nitride, graphite and silicon carbide powder, the second component includes: at least one of aluminum oxide, silicon dioxide, boron oxide, titanium dioxide and magnesium oxide powder, and the third component includes: at least one of nickel oxide, cobalt oxide, manganese dioxide and zirconium oxide powder.
[0007] In some possible embodiments, in the composite filler, the first component includes: at least one of 10wt% to 50wt% of boron nitride, 5wt% to 45wt% of graphite and 5wt% to 45wt% of silicon carbide powder; the second component includes: at least one of 5wt% to 40wt% of aluminum oxide, 20wt% to 70wt% of silicon dioxide, 1wt% to 10wt% of boron oxide, 5wt% to 25wt% of titanium dioxide and 5wt% to 25wt% of magnesium oxide powder; and the third component includes: at least one of 0.1wt% to 5wt% of nickel oxide, 0.1wt% to 10wt% of cobalt oxide, 0.1wt% to 10wt% of manganese dioxide and 0.5wt% to 15wt% of zirconium oxide powder.
[0008] In some possible embodiments, the film-forming substance includes at least one of 10 wt % to 40 wt % of silica sol, 10 wt % to 30 wt % of silicate, and 10 wt % to 50 wt % of phosphate.
[0009] In some possible embodiments, the coating composition further includes 0.01 wt % to 0.04 wt % of a surfactant and 0.5 wt % to 5 wt % of a dispersant.
[0010] In some possible embodiments, the surfactant includes at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate and sodium fatty acid methyl ester sulfonate; the dispersant includes at least one of sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate.
[0011] The embodiment of the present application also provides a coating, which is formed by curing the above coating composition.
[0012] The present application also provides a method for preparing a coating, and the method for preparing the coating comprises:
[0013] The first component, the second component and the third component are mixed and ground to obtain a composite filler, wherein the first component comprises at least one of boron nitride, graphite and silicon carbide powder, the second component comprises at least one of aluminum oxide, silicon dioxide, boron oxide, titanium dioxide and magnesium oxide powder, and the third component comprises at least one of nickel oxide, cobalt oxide, manganese dioxide and zirconium oxide powder;
[0014] Mixing 30 wt% to 70 wt% of a film-forming substance and 30 wt% to 70 wt% of a composite filler to obtain a coating composition; and
[0015] The coating composition is formed into a film layer on the surface of the metal substrate and heated and cured to form a coating.
[0016] In some possible embodiments, heating curing includes three steps of heating performed sequentially, the first step of heating at a temperature of 80-100°C for 1-2 hours; the second step of heating at a temperature of 120-150°C for 1-2 hours; the third step of heating at a temperature of 250-280°C for 1-2 hours.
[0017] In some possible embodiments, in the composite filler, the first component includes: at least one of 10wt% to 50wt% of boron nitride, 5wt% to 45wt% of graphite and 5wt% to 45wt% of silicon carbide powder; the second component includes: at least one of 5wt% to 40wt% of aluminum oxide, 20wt% to 70wt% of silicon dioxide, 1wt% to 10wt% of boron oxide, 5wt% to 25wt% of titanium dioxide and 5wt% to 25wt% of magnesium oxide powder; and the third component includes: at least one of 0.1wt% to 5wt% of nickel oxide, 0.1wt% to 10wt% of cobalt oxide, 0.1wt% to 10wt% of manganese dioxide and 0.5wt% to 15wt% of zirconium oxide powder; the film-forming substance includes: at least one of 10wt% to 40wt% of silica sol, 10wt% to 40% of silicate and 10wt% to 50% of phosphate.
[0018] In some possible embodiments, in the step of mixing 30wt% to 70wt% of a film-forming substance and 30wt% to 70wt% of a composite filler to obtain a coating composition, 0.01wt% to 0.04wt% of a surfactant and 0.5wt% to 5wt% of a dispersant are also added.
[0019] The coating with high lubricity formed by the coating composition provided in the embodiment of the present application is mainly used for isolation and protection on the surface of the metal substrate, and can improve the lubricity, high temperature resistance, oxidation resistance, corrosion resistance and hardness of the metal substrate surface. In particular, when low pressure chemical vapor deposition (LPCVD) produces polysilicon film, the coating can be effectively used to achieve the barrier of polysilicon and metal substrate, and the direct contact between polysilicon and metal substrate can be avoided, and the erosion of polysilicon to metal substrate can be slowed down. And in the process of polysilicon deposition, such coating has high lubricity, polysilicon is difficult to gather and grow up on the coating surface, and only less polysilicon can be deposited on the coating surface, and polysilicon is very small, and the bonding force with the coating is also poor. In this case, most of the polysilicon particles on the coating surface can be purged and discharged by gas purging in the non-process stage, which is convenient for cleaning, and it is difficult for polysilicon to gather and grow up, so it can also prevent the polysilicon that grows up from falling off and causing process pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1A flow chart of a method for preparing a coating provided in one embodiment of the present application.
[0021] Figure 2 This is a metallographic microscope photograph of polycrystalline silicon accumulated on the surface of a metal substrate without a coating.
[0022] Figure 3 This is a metallographic microscope photograph of the metal substrate and coating of Example 5 of the present application.
[0023] Figure 4 This is a real photo of the coating formed on the metal thermal insulation sheet in Example 5 of the present application.
[0024] The following specific implementation manner will further illustrate the embodiments of the present application in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the technical field belonging to the embodiments of the present application. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present application. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the raw materials, reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially.
[0026] It should be noted that all directional indications in the embodiments of the present application (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0027] It will be understood that when a layer is referred to as being "on" another layer, it can be directly on the other layer or intervening layers may be present therebetween. Conversely, when a layer is referred to as being "directly on" another layer, there are no intervening layers. When a component is referred to as being "fixed to," "mounted to," or "disposed on" another component, it can be directly on the other component or an intervening component may also be present.
[0028] Here, the embodiments of the present application are described with reference to the cross-sectional views, which are schematic diagrams of the idealized embodiments (and intermediate configurations) of the present application. Thus, it is foreseeable that the shapes of the diagrams are different due to manufacturing processes and / or tolerances. Therefore, the embodiments of the present application should not be interpreted as being limited to the specific shapes of the regions illustrated here, but should include deviations in shapes such as those produced due to manufacturing. The regions shown in the figures are themselves only schematic, and their shapes are not intended to illustrate the actual shapes of the devices, and are not intended to limit the scope of the present application.
[0029] Some embodiments of the present application are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0030] The embodiment of the present application provides a coating with high lubricity applied to the surface of a metal substrate, the coating is formed by curing a coating composition with high lubricity, the coating composition can be used on the surface of a metal substrate, the raw materials of the coating composition include: 30wt% to 70wt% of a film-forming substance and 30wt% to 70wt% of a composite filler, the composite filler is dispersed in the film-forming substance. The composite filler may include a variety of filler components, specifically including a first component, a second component and a third component. Among them, the first component may include at least one of boron nitride, graphite and silicon carbide powder, the second component may include at least one of aluminum oxide, silicon dioxide, boron oxide, titanium dioxide and magnesium oxide powder, and the third component may include at least one of nickel oxide, cobalt oxide, manganese dioxide and zirconium oxide powder.
[0031] The first component is chemically stable and does not react with amorphous silicon / polycrystalline silicon even in a high-temperature vapor deposition atmosphere. It also has a low friction coefficient, which makes it difficult for silicon to accumulate on the surface of the coating. The second component, as a stabilizer for the coating, can improve the hardness and density of the coating. The third component has a high thermal expansion coefficient and is highly active, so it is easy to combine with the metal surface, improving the adhesion and stability of the coating on the surface of the metal substrate. By compounding the high-temperature resistant ceramic particles of the above three components, the coating can have a high lubricity while effectively improving the heat resistance, hardness, oxidation resistance, corrosion resistance, wear resistance, adhesion and stability of the coating. The formed coating can have excellent comprehensive performance and can also effectively improve the service life of the coating.
[0032] In some embodiments, based on the total mass of the composite filler as 100wt%, the first component may include: at least one of 10wt% to 50wt% of boron nitride, 5wt% to 45wt% of graphite and 5wt% to 45wt% of silicon carbide powder; the second component may include: at least one of 5wt% to 40wt% of aluminum oxide, 20wt% to 70wt% of silicon dioxide, 1wt% to 10wt% of boron oxide, 5wt% to 25wt% of titanium dioxide and 5wt% to 25wt% of magnesium oxide powder; the third component may include: at least one of 0.1wt% to 5wt% of nickel oxide, 0.1wt% to 10wt% of cobalt oxide, 0.1wt% to 10wt% of manganese dioxide and 0.5wt% to 15wt% of zirconium oxide powder.
[0033] In the embodiment of the present application, the film-forming material is mainly an inorganic adhesive, for example, it may include at least one of silica sol, silicate and phosphate.
[0034] Among them, silica sol is used as a film-forming material, which has low viscosity and strong permeability, so it has very good dispersibility and permeability when mixed with composite fillers; and because the colloidal particles of silica sol are fine (usually 10nm to 20nm), they have a large specific surface area and can be used as a carrier of composite fillers; in addition, when the silica sol is solidified, the colloidal particles can be firmly attached to the surface of the object, and silicon-oxygen bonds are formed between the particles, which has excellent adhesion, high temperature resistance, anti-fouling and dust resistance, and aging resistance, and has fire resistance. For example, silica sol can be sodium silica sol, potassium silica sol, ammonia silica sol, etc.
[0035] Silicate is used as a film-forming substance to form a silicate coating, which has high bonding strength with the metal substrate, excellent high temperature resistance, good weather resistance, and high cost performance. For example, the silicate can be ammonium silicate, lithium silicate, sodium silicate, potassium silicate, etc.
[0036] The use of phosphate as a film-forming substance has the advantages of good solvent resistance, wear resistance, aging resistance, flame resistance, heat resistance, excellent metal adhesion, high bonding strength, excellent corrosion resistance, good water resistance and oil resistance. The formed phosphate coating is an inorganic coating with high mechanical strength, good thermal stability, corrosion resistance, non-toxic and environmentally friendly. The general formula of phosphate is M m O nx P2O 5y H2O, wherein M is a metal atom, m and n are positive integers, x and y are positive real numbers, and the ratio of the metal atom content to the phosphorus atom content, i.e., M / P, is generally within the range of 0.25 to 1. Phosphates may be, for example, potassium dihydrogen phosphate, aluminum dihydrogen phosphate, trisodium phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and the like.
[0037] In some embodiments, a composition of silica sol, silicate and phosphate can be used as a common film-forming substance. Compounding silica sol, silicate and phosphate as a film-forming substance can reduce the curing temperature and make the formed coating have excellent comprehensive properties.
[0038] In some embodiments, based on the total mass of the film-forming material being 100 wt %, the film-forming material may include: 10 wt % to 40 wt % of silica sol, 10 wt % to 40 wt % of silicate, and 10 wt % to 50 wt % of phosphate.
[0039] The mass ratio of the film-forming substance to the composite filler is a key parameter in the coating composition formulation, which affects the dispersibility and film-forming property of the filler, and ultimately affects the corrosion resistance, lubricity, heat resistance and mechanical properties of the coating. The embodiment of the present application controls the mass of the two within the aforementioned range and adjusts according to actual needs, so that the composite filler can be dispersed more evenly in the film-forming substance, is less likely to agglomerate, and is less likely to crack after film formation. At the same time, the coating formed has excellent comprehensive performance.
[0040] In some embodiments, the coating composition may also include 0.01wt% to 0.04wt% of a surfactant, specifically, the surfactant includes at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium fatty acid methyl ester sulfonate, etc. The above surfactants are easily soluble in water, not easily soluble in organic systems (such as ether, petroleum ether, etc.), suitable for the aqueous system of this formula, and the volatile matter of the aqueous system slurry is extremely low, environmentally friendly and harmless. When their concentration reaches the critical micelle concentration (CMC), the surfactant molecules will spontaneously aggregate to form micelles, which can change the wetting properties of the solid surface, increase the wetting ability of the liquid to the solid, help to disperse the solid particles in the liquid, and prevent the particles from aggregating and precipitating. By adding a surfactant, the surface tension of the liquid surface can be reduced, and emulsification and dispersion can be performed to further improve the dispersibility of the system and the surface lubricity of the formed coating.
[0041] In some embodiments, the coating composition may further include 0.5 wt% to 5 wt% of a dispersant, specifically, the dispersant includes at least one of sodium tripolyphosphate (STPP), sodium hexametaphosphate, sodium pyrophosphate, etc. For example, sodium tripolyphosphate is an amorphous water-soluble linear polyphosphate with a chemical formula of Na5P3O 10 , molecular weight is 367.864, it is easily soluble in water and the aqueous solution is alkaline. The above types of dispersants contain polyphosphate chains, which can form stable complexes with metal ions, making the coating easier to form a film. Since the aqueous solution of the above dispersants is alkaline, it can also play a role in regulating the pH balance when the system is acidic. By adding an appropriate amount of dispersant, it can aid grinding, dilute and improve suspension stability, significantly improve the fluidity of ceramic slurry, control the viscosity of glaze slurry, improve the thixotropic properties of glaze, overcome glaze precipitation, and improve wettability.
[0042] The above-mentioned coating composition is mainly applied to the surface of a metal substrate and cured to form a coating with high lubricity. Specifically, the coating with high lubricity mainly plays an isolating and protective role, improving the lubricity, high temperature resistance, oxidation resistance, corrosion resistance and hardness of the metal substrate surface. In particular, when producing polycrystalline silicon film by low-pressure chemical vapor deposition (LPCVD), the application of the coating with high lubricity can effectively isolate the direct contact between polycrystalline silicon and the metal substrate, reducing the erosion of the polycrystalline silicon on the metal substrate; at the same time, since the coating has high lubricity, it can reduce the accumulation of polycrystalline silicon on the surface of metal parts.
[0043] The coating formed by the coating composition of the embodiment of the present application has a strong bonding force with the metal substrate and has good barrier properties, can achieve the barrier between polysilicon and the metal substrate, can avoid direct contact between polysilicon and the metal substrate, and slow down the erosion of the metal substrate by polysilicon. In addition, during the process of polysilicon deposition, such coating has high lubricity, polysilicon is difficult to gather and grow on the coating surface, only a small amount of polysilicon can be deposited on the coating surface, and the polysilicon is very small, and the bonding force with the coating is also poor. In this case, most of the polysilicon particles on the coating surface can be blown away by gas purge in the non-process stage, which is convenient for cleaning, and it is difficult for polysilicon to gather and grow, so it can also prevent the accumulated polysilicon from falling off and causing process pollution.
[0044] See also Figure 1 Based on the same inventive concept, the present application also provides a method for preparing the aforementioned coating, and the preparation method specifically comprises the following steps:
[0045] Step S1, mixing and grinding a first component, a second component and a third component to obtain a composite filler, wherein the first component includes: at least one of boron nitride, graphite and silicon carbide powder, the second component includes: at least one of aluminum oxide, silicon dioxide, boron oxide, titanium dioxide and magnesium oxide powder, and the third component includes: at least one of nickel oxide, cobalt oxide, manganese dioxide and zirconium oxide powder.
[0046] Specifically, the fillers of the above three components are fully mixed, distilled water or alcohol is added, ball milled for 1 to 3 hours, the rotation speed is 200 to 400 r / min, and dried at 80 to 120° C. for 16 to 24 hours to finally obtain a composite filler.
[0047] In some embodiments, based on the total mass of the composite filler being 100wt%, in the composite filler, the first component includes: at least one of 10wt% to 50wt% of boron nitride, 5wt% to 45wt% of graphite and 5wt% to 45wt% of silicon carbide powder; the second component includes: at least one of 5wt% to 40wt% of aluminum oxide, 20wt% to 70wt% of silicon dioxide, 1wt% to 10wt% of boron oxide, 5wt% to 25wt% of titanium dioxide and 5wt% to 25wt% of magnesium oxide powder; and the third component includes: at least one of 0.1wt% to 5wt% of nickel oxide, 0.1wt% to 10wt% of cobalt oxide, 0.1wt% to 10wt% of manganese dioxide and 0.5wt% to 15wt% of zirconium oxide powder. Step S2, 30wt% to 70wt% of the film-forming substance and 30wt% to 70wt% of the composite filler are mixed to obtain a coating composition.
[0048] Specifically, the composite filler is evenly dispersed in the film-forming material by high-speed stirring with a stirrer, the rotation speed may be 200 to 600 r / min, and the stirring time may be 30 to 120 min.
[0049] In some embodiments, the film-forming substance may include at least one of 10 wt % to 40 wt % of silica sol, 10 wt % to 40 wt % of silicate, and 10 wt % to 50 wt % of phosphate.
[0050] In some embodiments, the coating composition may further include 0.01 wt% to 0.04 wt% of a surfactant and 0.5 wt% to 5 wt% of a dispersant.
[0051] Step S3, forming a film layer of the coating composition on the surface of the metal substrate and heating and curing it to form a coating.
[0052] In step S3, heating curing includes three heating steps performed in sequence. The first step is heated at a temperature of 80-100°C for 1-2 hours; the second step is heated at a temperature of 120-150°C for 1-2 hours; and the third step is heated at a temperature of 250-280°C for 1-2 hours.
[0053] Specifically, the coating composition can be applied to the surface of the metal substrate by brushing, dipping or spraying.
[0054] After natural drying, it is placed in an oven and heated in sequence according to the above three heating conditions, and then naturally cooled to room temperature in the oven to obtain a coating with high lubricity.
[0055] The method for preparing a coating with high lubricity in the embodiment of the present application has a low processing temperature, low cost, and is beneficial to reducing the risk of deformation and oxidation of the metal substrate during heating. It is particularly suitable for producing polysilicon films by low-pressure chemical vapor deposition (LPCVD).
[0056] The metal parts coating solution provided in the embodiment of the present application has lower preparation cost and no restrictions on the preparation environment compared to PVD and CVD solutions. It is a brand-new technical solution for metal parts deposited by LPCVD in the TOPCon process to resist polysilicon corrosion and pollution. Moreover, it can meet all-weather, low-restriction coating processing, achieve low-cost coating spraying and sintering, and has a simple process and strong applicability. It can realize the surface coating preparation of large parts, complex structural parts, and special-shaped parts. In addition, the coating solution of this embodiment realizes the preparation of the coating on the basis of existing metal parts, thereby achieving the effect of corrosion resistance. Therefore, there is no need to replace or develop new materials, and the cost is low and the applicability is strong.
[0057] The embodiments of the present application are further described below through specific examples.
[0058] Embodiment 1:
[0059] (1) 15 wt% of boron nitride and 10 wt% of silicon carbide powder are mixed, and 15 wt% of aluminum oxide powder, 50 wt% of silicon dioxide, 2 wt% of boron oxide, 5 wt% of titanium dioxide, 2 wt% of nickel oxide, and 1 wt% of manganese dioxide powder are mixed, and alcohol is added and ball-milled for 2 h at a speed of 300 r / min and dried at 100° C. for 20 h to obtain a composite filler (i.e., component A).
[0060] (2) 40 wt% of silica sol, 40 wt% of silicate and 20 wt% of phosphate are mixed to obtain a film-forming substance (i.e. component B).
[0061] (3) 60 wt% of component A, 38.98 wt% of component B, 0.02 wt% of sodium lauryl sulfate and 1 wt% of sodium tripolyphosphate were uniformly dispersed by stirring at high speed of 350 r / min for 90 minutes to obtain a high lubricity coating composition (i.e., component C).
[0062] (4) Component C is sprayed on the surface of the metal part, and after natural drying, it is placed in an oven and dried at 80°C for 1 hour, 120°C for 1 hour, and 250°C for 1 hour, and naturally cooled to room temperature in the oven to obtain a high lubricity coating.
[0063] Embodiment 2:
[0064] The difference from Example 1 is that: 10 wt % of boron nitride, 5 wt % of graphite and 10 wt % of silicon carbide powder are mixed in component A. For the rest, please refer to Example 1 for details.
[0065] Embodiment 3:
[0066] The difference from Example 1 is that 15 wt % of boron nitride, 5 wt % of graphite and 5 wt % of silicon carbide powder are mixed in component A. For the rest, please refer to Example 1 for details.
[0067] Embodiment 4:
[0068] (1) 15 wt% of boron nitride, 5 wt% of graphite, and 5 wt% of silicon carbide powder were mixed, and 15 wt% of aluminum oxide powder, 50 wt% of silicon dioxide, 2 wt% of boron oxide, 5 wt% of titanium dioxide, 2 wt% of nickel oxide, and 1 wt% of manganese dioxide powder were mixed, and alcohol was added and ball-milled for 2 h at a speed of 300 r / min and dried at 100° C. for 20 h to obtain component A.
[0069] (2) 33.4 wt% of silica sol, 33.3 wt% of silicate and 33.3 wt% of phosphate were mixed to obtain component B.
[0070] (3) 60 wt% of component A, 38.98 wt% of component B, 0.02 wt% of sodium lauryl sulfate and 1 wt% of sodium tripolyphosphate were uniformly dispersed by stirring at high speed of 350 r / min for 90 minutes to obtain component C.
[0071] (4) Component C is sprayed on the surface of the metal part, and after natural drying, it is placed in an oven and dried at 80°C for 1 hour, 120°C for 1 hour, and 250°C for 1 hour, and naturally cooled to room temperature in the oven to obtain a high lubricity coating.
[0072] Embodiment 5:
[0073] The difference from Example 4 is that: 20 wt % of silica sol, 40 wt % of silicate and 40 wt % of phosphate are mixed in component B. For the rest, please refer to Example 4 for details.
[0074] Embodiment 6:
[0075] (1) 15 wt% of boron nitride, 5 wt% of graphite, and 5 wt% of silicon carbide powder were mixed, and 15 wt% of aluminum oxide powder, 50 wt% of silicon dioxide, 2 wt% of boron oxide, 5 wt% of titanium dioxide, 2 wt% of nickel oxide, and 1 wt% of manganese dioxide powder were mixed, and alcohol was added and ball-milled for 2 h at a speed of 300 r / min and dried at 100° C. for 20 h to obtain component A.
[0076] (2) 40 wt% of silica sol, 40 wt% of silicate and 20 wt% of phosphate are mixed to obtain component B.
[0077] (3) 65 wt% of component A, 33.98 wt% of component B, 0.02 wt% of sodium lauryl sulfate and 1 wt% of sodium tripolyphosphate were uniformly dispersed by stirring at high speed of 350 r / min for 90 minutes to obtain component C.
[0078] (4) Component C is sprayed on the surface of the metal part, and after natural drying, it is placed in an oven and dried at 80°C for 1 hour, 120°C for 1 hour, and 250°C for 1 hour, and naturally cooled to room temperature in the oven to obtain a high lubricity coating.
[0079] Embodiment 7:
[0080] The difference from Example 6 is that 55 wt% of component A and 43.98 wt% of component B are selected in component C. For the rest, please refer to Example 6 for details.
[0081] Comparative Example 1
[0082] The LPCVD equipment directly uses metal heat shields without coating.
[0083] like Figure 2 As shown, it is a metallographic microscope photo of the metal heat shield (i.e., metal substrate) in the LPCVD device in Comparative Example 1 without a coating. Figure 2 It can be seen that after the polysilicon grows to the heat insulation sheet, the polysilicon causes corrosion to the substrate of the metal heat insulation sheet.
[0084] like Figure 3 The figure shows the metallographic microscope photos of the metal substrate and the coating after the metal substrate with the coating in Example 5 is applied to the LPCVD equipment. Figure 3 It can be seen that there is no obvious interface between the metal substrate and the coating, indicating that the coating can stably adhere to the surface of the metal substrate. In addition, a small amount of fine polysilicon particles float on the surface of the coating, indicating that the coating can reduce the deposition of polysilicon. Even a small amount of fine polysilicon particles can be blown away by non-process airflow.
[0085] like Figure 4 The following is a photo of a metal heat shield in a LPCVD device having a coating formed on its surface. Figure 4 It can be seen that the coating composition has good film-forming properties and the formed coating has high surface quality.
[0086] The corresponding test data of Examples 1 to 7 are shown in Table 1.
[0087] Table 1
[0088]
[0089] Adhesion test method: pull-off method, the instrument is KS-M coating adhesion tester.
[0090] Thermal shock stability test method: Heat the sample to 800°C, then take out the sample and cool it to room temperature in air, and repeat this cycle.
[0091] Salt spray resistance test: 5% NaCl salt spray test.
[0092] Coating thickness test method: The coating thickness is measured using the Hall effect and eddy current effect. The measuring instrument is the Linshang LS221 coating thickness gauge.
[0093] It can be seen from Examples 1 to 3 that the salt spray resistance test time of the metal substrate after the coating is much longer than that of the bare metal substrate, and the friction coefficient of the metal substrate after the coating is set is smaller than that of the metal substrate without the coating. In particular, Example 3 shows very excellent thermal shock stability and adhesion, which is mainly due to the regulation of the component ratio of boron nitride, graphite and silicon carbide. Therefore, component A comprising 15wt% boron nitride, 5wt% graphite and 5wt% silicon carbide powder is preferred.
[0094] It can be seen from Examples 3 to 5 that the metal substrates after coating have a much longer salt spray resistance test time than the bare metal substrates, and the friction coefficient and 600°C water-cooled thermal shock stability are very good. The coating adhesion of Example 5 is better, mainly because the component ratio of silica sol, silicate and phosphate is adjusted, and the ratio of silicate and phosphate is increased, thereby improving the adhesion of the coating. Therefore, the ratio of the film-forming material in Example 5 is conducive to improving the adhesion of the coating.
[0095] It can be seen from Examples 5 to 7 that the metal substrate with the coating has a much longer salt spray resistance test time than the bare metal substrate. In terms of coating adhesion, 600°C water-cooled thermal shock stability and friction coefficient, Example 5 is better, mainly because the ratio of component A and component B in component C is regulated. Therefore, component C comprising 60wt% component A and 38.98wt% component B is preferred.
[0096] It can be seen that after the coating of the embodiment of the present application is used to achieve the barrier between polysilicon and the metal substrate, the direct contact between polysilicon and the metal substrate can be avoided, and the erosion of the metal substrate by polysilicon can be slowed down. In addition, during the process of polysilicon deposition, this type of coating has high lubricity, and it is difficult for polysilicon to aggregate and grow on the surface of the coating. Only a small amount of polysilicon can be deposited on the surface of the coating, and the polysilicon is very small, and the bonding force with the coating is also poor. In this case, most of the polysilicon particles on the surface of the coating can be purged and discharged by gas purging in the non-process stage, which is convenient for cleaning, and it is difficult for polysilicon to aggregate and grow, so it can also prevent the aggregated and grown polysilicon from falling off and causing process pollution.
[0097] The above descriptions are some specific implementations of the present application, but they are not limited to these implementations in actual application. For ordinary technicians in this field, other variations and changes made according to the technical concept of the present application should all fall within the protection scope of the present application.
Claims
1. A coating composition, characterized in that The raw materials of the coating composition include: 30wt% to 70wt% of a film-forming substance and 30wt% to 70wt% of a composite filler, wherein the composite filler includes: a first component, a second component and a third component, the first component includes: at least one of boron nitride, graphite and silicon carbide powder, the second component includes: at least one of aluminum oxide, silicon dioxide, boron oxide, titanium dioxide and magnesium oxide powder, and the third component includes: at least one of nickel oxide, cobalt oxide, manganese dioxide and zirconium oxide powder.
2. The coating composition according to claim 1, characterized in that In the composite filler, The first component comprises: at least one of 10wt% to 50wt% of boron nitride, 5wt% to 45wt% of graphite and 5wt% to 45wt% of silicon carbide powder; The second component comprises at least one of 5wt% to 40wt% of aluminum oxide, 20wt% to 70wt% of silicon dioxide, 1wt% to 10wt% of boron oxide, 5wt% to 25wt% of titanium dioxide and 5wt% to 25wt% of magnesium oxide powder; The third component includes at least one of 0.1 wt% to 5 wt% nickel oxide, 0.1 wt% to 10 wt% cobalt oxide, 0.1 wt% to 10 wt% manganese dioxide and 0.5 wt% to 15 wt% zirconium oxide powder.
3. The coating composition according to claim 1, characterized in that The film-forming substance comprises at least one of 10wt% to 40wt% of silica sol, 10wt% to 30% of silicate and 10wt% to 50% of phosphate.
4. The coating composition according to claim 1, characterized in that The coating composition further comprises 0.01 wt% to 0.04 wt% of a surfactant and 0.5 wt% to 5 wt% of a dispersant.
5. A coating, characterized in that: The coating layer is formed by curing the coating composition according to any one of claims 1 to 4.
6. A method for preparing a coating, characterized in that: include: The first component, the second component and the third component are mixed and ground to obtain a composite filler, wherein the first component comprises at least one of boron nitride, graphite and silicon carbide powder, the second component comprises at least one of aluminum oxide, silicon dioxide, boron oxide, titanium dioxide and magnesium oxide powder, and the third component comprises at least one of nickel oxide, cobalt oxide, manganese dioxide and zirconium oxide powder; Mixing 30 wt % to 70 wt % of a film-forming substance and 30 wt % to 70 wt % of the composite filler to obtain a coating composition; and The coating composition is formed into a film layer on the surface of a metal substrate and heated and cured to form the coating layer.
7. The method for preparing the coating according to claim 6, characterized in that: The heating curing comprises three heating steps performed sequentially, wherein the first step is heated at a temperature of 80-100°C for 1-2 hours; the second step is heated at a temperature of 120-150°C for 1-2 hours; and the third step is heated at a temperature of 250-280°C for 1-2 hours.
8. The method for preparing the coating according to claim 6, characterized in that: In the composite filler, The first component comprises: at least one of 10wt% to 50wt% of boron nitride, 5wt% to 45wt% of graphite and 5wt% to 45wt% of silicon carbide powder; The second component comprises at least one of 5wt% to 40wt% of aluminum oxide, 20wt% to 70wt% of silicon dioxide, 1wt% to 10wt% of boron oxide, 5wt% to 25wt% of titanium dioxide and 5wt% to 25wt% of magnesium oxide powder; The third component comprises: at least one of 0.1wt% to 5wt% nickel oxide, 0.1wt% to 10wt% cobalt oxide, 0.1wt% to 10wt% manganese dioxide and 0.5wt% to 15wt% zirconium oxide powder; The film-forming substance comprises at least one of 10wt% to 40wt% of silica sol, 10wt% to 40wt% of silicate and 10wt% to 50% of phosphate.
9. The method for preparing the coating according to claim 6, characterized in that: In the step of mixing 30wt% to 70wt% of the film-forming substance and 30wt% to 70wt% of the composite filler to obtain the coating composition, 0.01wt% to 0.04wt% of a surfactant and 0.5wt% to 5wt% of a dispersant are also added.
10. A coating device, characterized in that: The invention comprises a heating device and a metal component arranged in the heating device, wherein the metal component has a coating, and the coating is the coating according to claim 5 or a coating obtained by the coating preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Ceramic paint and preparation method thereof as well as heating furnace tube
CN103265264A
Non-Cr high-temperature infrared energy-saving coating, and preparation method and application thereof
CN103289452A
Anti-oxidation coating for steel billet with high emissivity and preparation method of anti-oxidation coating
CN104498683A
High-temperature-resisting infrared heat energy-saving coating and preparation method thereof
CN108250811A
Anti-coking and anti-slagging coating material for four tubes of boiler and preparation method of anti-coking and anti-slagging coating material
CN109486414A
Cited By
High-temperature-resistant coating capable of being subjected to low surface treatment and preparation method thereof
CN122326024A
